Oxide Materials at the Two-Dimensional Limit - Netzer, Falko P.; Fortunelli, Alessandro (Springer Series in Materials Science,, 2016)
This book summarizes the current knowledge of two-dimensional oxide materials. The fundamental properties of 2-D oxide systems are explored in terms of atomic structure, electronic behavior and surface chemistry.  The concept of polarity in determining the stability of 2-D oxide layers is examined, charge transfer effects in ultrathin oxide films are reviewed as well as the role of defects in 2-D oxide films. The novel structure concepts that apply in oxide systems of low dimensionality are addressed,  and a chapter giving an overview of state-of-the-art theoretical methods for electronic structure determination of nanostructured oxides is included. Special emphasis is given to a balanced view from the experimental and the theoretical side. Two-dimensional materials, and 2-D oxides in particular, have outstanding behavior due to dimensionality and proximity effects. Several chapters treat prototypical model systems as illustrative examples to discuss the peculiar physical and chemical properties of 2-D oxide systems. The chapters are written by renowned experts in the field.